Chronic recurrent multifocal osteomyelitis in children and adults: current understanding and areas for development. (6th April 2017) - Roderick, Marion R; Sen, Ethan S; Ramanan, Athimalaipet V
Abstract: Since the first descriptions of chronic recurrent multifocal osteomyelitis in the 1970s, there have been numerous case reports in the literature; both unusual case reports and case series from all over the world. Our understanding of the pathogenesis has significantly changed, with it now being regarded as an autoinflammatory condition. Treatment options have also expanded, but little progress has been made in developing the evidence for treatments. Advancing gene studies have provided a mouse model, but the quest for a single gene to match the phenotype has been elusive. Early cohorts of patients have grown up into adults, allowing prospective data to inform the expected outcomes.